CRLF2 and JAK2 in B-Progenitor Acute Lymphoblastic Leukemia: A Novel Association in Oncogenesis - Roll, J. Devon (2010)
Expression of cytokine receptor-like factor 2 (CRLF2) has recently been shown to be upregulated as well as mutated in populations of B-ALL, including Down syndrome (DS-ALL) patients, which lack recurring chromosomal translocations. Increased CRLF2 expression associates with JAK2 mutation, a combination that transforms hematopoietic cells, suggesting that mutant JAK2 and CRLF2 may cooperate to contribute to B-ALL formation. Importantly, elevated CRLF2 expression correlates with poor outcome in high-risk B-ALL patients. Therefore, CRLF2 may provide a new prognostic marker for high-risk B-ALL and inhibition of CRLF2/JAK2 signaling may represent a therapeutic approach for this population of ALL patients.